PENGARUH KEBERAGAMAN PRODUK DAN LOKASI TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN PRODUK OMAH FURNITURE - Mutaqin, Annisa Zahra; Ali, Hapzi; Khan, Muhammad Asif; Sawitri, Ni Nyoman; Navanti, Dovina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research is used to measure the effect of product diversity and location on customer satisfaction through purchasing decisions. This research is a quantitative study in which the objects used are Omah Furniture consumers. The number of samples used in this study were 136 respondents. The design used is hypothesis testing using the Structural Equation Modeling (SEM) method - SmartPLS 4.0. The results of this study explain that the variables of product diversity, location, and purchasing decisions have a positive and significant effect on customer satisfaction. This study provides advice that companies should pay more attention to product diversity and location to increase customer satisfaction and company competitiveness.